2008
DOI: 10.1348/014466607x269748
|View full text |Cite
|
Sign up to set email alerts
|

Do as we say and as we do: The interplay of descriptive and injunctive group norms in the attitude–behaviour relationship

Abstract: were conducted to tease apart the relative effects of descriptive and injunctive group norms. In both studies, university students' attitudes towards current campus issues were obtained, descriptive and injunctive group norms were manipulated, and participants' postmanipulation attitudes, behavioural willingness, and behaviour were assessed. Study 2 also examined the role of norm source (i.e., ingroup vs. outgroup injunctive and descriptive norms). In both studies, injunctive and descriptive ingroup norms inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
254
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(285 citation statements)
references
References 48 publications
(106 reference statements)
26
254
2
3
Order By: Relevance
“…As expected and in line with studies that have investigated aligned normative injunctive and descriptive normative messages (i.e., [24,47]), a normative message emphasizing both one's injunctive and personal norms resulted in the lowest uptake of free plastic bags. Although the combined normative message showed the largest change in use of plastic bags, the difference was significant compared to the standard environmental message only and not compared to the injunctive or personal normative message only.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As expected and in line with studies that have investigated aligned normative injunctive and descriptive normative messages (i.e., [24,47]), a normative message emphasizing both one's injunctive and personal norms resulted in the lowest uptake of free plastic bags. Although the combined normative message showed the largest change in use of plastic bags, the difference was significant compared to the standard environmental message only and not compared to the injunctive or personal normative message only.…”
Section: Discussionsupporting
confidence: 83%
“…In another study, Smith and Louis [47] showed an interaction effect between the injunctive and descriptive norms: the impact of a salient injunctive norm to sign a petition against full-fee places for domestic undergraduate students was stronger when the descriptive norm to support this signing was salient as well. Finally, in three large scale surveys, Thøgersen [48] consistently found that the effect of the injunctive and descriptive norms combined were stronger than their additive effects for explaining a diversity of self-reported pro-environmental behaviors.…”
Section: Persuasive Normative Messages: Combined Injunctive and Persomentioning
confidence: 95%
See 1 more Smart Citation
“…The measure of symptom norms consisted of 4 items adapted from various sources (e.g., Cruwys, Haslam, Fox, & McMahon, 2015;Smith & Louis, 2008) that asked participants to rate how likely it would be for other people with depression to engage in four kinds of symptom-related cognitions (e.g. "Keep thinking negative and unhelpful thoughts") and behaviors (e.g.…”
Section: Symptom Normsmentioning
confidence: 99%
“…These behaviourally important descriptive social norms (i.e. what most people do and accept, regardless of whether it is legal) are likely to be influenced by formal norms and rules (Smith, 2008). The successful adoption of new legislation and social rules relies on this mechanism: a formal norm modifies or responds to a descriptive norm, which in turn modulates individual behaviour.…”
Section: Ideologymentioning
confidence: 99%